PENGARUH KOMPETENSI, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KREATIVITAS KERJA PEGAWAI INSPEKTORAT KABUPATEN KUBU RAYA - B2042142019, ANDRIANI (Equator Journal of Management and Entrepreneurship (EJME), 2017)
The purpose of this study is to examine and analyze the influence of competence, organizational culture and job satisfaction on the work creativity of Inspektorat Kabupaten Kubu Raya. This form of research is using descriptive with comparative causal approach. Data collection using primary data in the form of questionnaires and interviews and secondary data in the form of data sourced from Inspektorat Kabupaten Kubu Raya. The sample uses a census. The sample in this research is all employees at Inspektorat Kabupaten Kubu Raya as many as 37 people. The results of this study indicate that competence affects the work creativity of employees Inspektorat, organizational culture influence on employee work creativity Inspectorate and job satisfaction have an effect on to work creativity of Inspektorat Kabupaten Kubu Raya.     Keywords: Competence, Organizational Culture, Job Satisfaction And Work Creativity.